Comparison of Techniques for Extracting Viral RNA in Plasma for Dengue Diagnosis by Reverse Transcriptase-PCR - Palmares, Aaron Jan S.; Chan, Veronica F.; Baclig, Michael O. (Asian Journal of Biological and Life Sciences, 2017)
This study aims to determine if the rate of RT-PCR detection of Dengue virus from clinical plasma would vary between the RNA extracts of QIAamp® Viral RNA and TRIzol® LS in the first week of Dengue infection. Plasma samples from 31 individuals clinically suspected of being infected with dengue virus in day 1 to 7 of fever onset were extracted for RNA using the protocol of QIAamp® Viral RNA and TRIzol® LS. The paired RNA extracts of plasma samples were analyzed for the presence of Dengue virus RNA using RT-PCR. Out of 31 samples, a significantly higher rate of RT-PCR detection was obtained with QIAamp® than TRIzol® (74% vs. 48%, p=0.039). In comparison to Dengue NS1 antigen positivity, a significantly lower rates of RT-PCR detection was obtained with TRIzol® (77% vs. 48%, p=0.035), while there was no significant difference with QIAamp® (77% vs. 74%, p=1.000). In comparison to Dengue IgM/IgG antibody positivity, the rates of RT-PCR detection with QIAamp® was significantly higher (42% vs. 74%, p=0.031) while there was no significant difference with TRIzol® (42% vs. 48%, p=0.832).These results suggest that RNA extraction using QIAamp® Viral RNA provides more sufficiently pure RNA template for a conventional RT-PCR than TRIzol® LS.
Keywords: Dengue virus; Diagnosis; NS1 antigen; IgM/IgG antibody; RNA extraction; RT-PCR